Influence of Acidic Functional Groups of Activated Carbon and Solution pH on Cadmium Ion Adsorption - YOSHIHARA, Kazuya; FUJIMURA, Yoko; TATSUMOTO, Hideki; MACHIDA, Motoi; AIKAWA, Masami; ZAINI, Muhammad Abbas AHMAD (Journal of Ion Exchange, 2008)
Adsorption of cadmium ions from aqueous solutions onto two kinds of activated carbon, one with an enhanced amount of acidic functional groups prepared by oxidation with nitric acid treatment (oxidized carbon) and the other with no acidic functional group prepared by heating in a helium flow (out-gassed carbon), was investigated to clarify the influence of acidic functional groups on cadmium ion adsorption. The uptake of cadmium ions on the oxidized carbon was greater than that on the out-gassed carbon. Protons were released nearly stoichiometrically accompanying cadmium ion adsorption for the former, while no such phenomenon was observed for the latter. In desorption, the exchange of adsorbed cadmium ions with protons was observed only for the oxidized carbon. The amount of adsorbed cadmium ions increased with increasing solution pH for both the activated carbons, although adsorption started at a lower pH value for the oxidized carbon.